Exploring Self-Potential and Business Potential as an Effort to Create Womenpreneurship - Sofie Yunida Putri; Tantina Haryati; Acynthia Ayu Wilasittha (Future Science, 2022)
Sidoarjo Regency held a funding program for women's business groups targeted at housewives domiciled in Sidoarjo Regency, the funding was packaged in the form of the Independent Women's Business Card Program - KURMA - and will be given in the form of an Award to Independent Women Business Groups based on RT in Sidoarjo Regency through Administrative and technical assessments are carried out in stages from the village level to the district level, so it is necessary to assess the business potential and business interests of housewives in the surrounding environment. This community service activity was carried out by distributing questionnaires to mothers of Family Welfare Development (PKK) in Bligo village, RT 21, RW 08, Candi District, Sidoarjo Regency. The questionnaire was distributed with the aim that local PKK women were able to explore their potential because the main problem experienced was that there was a funding program organized by the local government, but these women still did not know the business potential and business interests they had. to obtain funding for the Mandiri Women's Business Card. Based on the service activities that we carried out, the results of the service showed that the most business potential in the local environment was in the culinary field, while the business interests of PKK women in the local area were businesses engaged in trading. Therefore, selling food is a business breakthrough that is considered the most appropriate according to the potential and interests of the existing business.